High-stability anisotropic conductive adhesive film and preparation method thereof
The anisotropic conductive adhesive film with a specific composition and preparation method addresses bonding strength and aging issues, achieving high peel strength and conductivity for extended service life in electronic packaging.
Patent Information
- Application Number
- CN202411383904.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing anisotropic conductive films suffer from low bonding strength, high resistivity, insufficient moisture and heat aging resistance, and short service life, limiting their application in electronic packaging.
A highly stable anisotropic conductive adhesive film composed of specific components including acrylate-terminated hyperbranched silicone-modified polyurethane, meso-tetramethyl-meso-tetraaminophenyl calix[4]pyrrole, and conductive particles, with a preparation method involving mixing, degassing, and drying to form an interpenetrating network structure.
The film exhibits high peel strength, good conductivity, and extended service life with enhanced resistance to moisture and heat aging, suitable for continuous large-scale production.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of conductive adhesive films, and in particular to a highly stable anisotropic conductive adhesive film and a preparation method thereof. Background Art
[0002] Anisotropic conductive film (ACF) is a new type of microelectronic component connection material, composed of resin, conductive filler, initiator and curing agent. It has the characteristics of low curing temperature, simple interconnection process and ultra-fine pitch. It is an important electronic packaging material to replace soldering and is widely used in the design of household electronic products, especially in liquid crystal displays (LCDs). It can be used to form a binding structure between the display panel and the circuit layer.
[0003] Existing anisotropic conductive adhesive films have more or less defects such as low bonding strength, high resistivity, insufficient resistance to moisture and heat aging, and short service life. In order to solve the above problems, the Chinese invention patent with application publication number CN118325525A discloses a highly stable ACF adhesive that can be stored for a long time and its preparation method. The ACF adhesive is processed from the following raw materials in parts by weight: 10 to 30 parts of tert-butyl cyclohexyl acrylate modified polytetrafluoroethylene, 20 to 50 parts of modified polymethyl methacrylate, 1 to 10 parts of conductive particles, 10 to 30 parts of rubber, 20 to 40 parts of silane coupling agent, 5 to 10 parts of the first solvent, and 1 to 10 parts of the first initiator. The invention adds tert-butyl cyclohexyl acrylate modified polytetrafluoroethylene to acrylate ACF, which can effectively improve the processing performance of polytetrafluoroethylene and its compatibility with other materials, and also improve the waterproofness of acrylate ACF, which is of great significance for the design and preparation of composite materials and can meet the application needs of different fields. However, the moisture-heat aging resistance and electrical conductivity of the ACF glue still need to be further improved.
[0004] It can be seen that the development of a highly stable anisotropic conductive film with high peel strength, good conductivity, sufficient moisture and heat aging resistance and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the anisotropic conductive film field. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a highly stable anisotropic conductive adhesive film having high peel strength, good conductivity, sufficient resistance to moisture and heat aging, and long service life, and a preparation method thereof.
[0006] To achieve the above object, the technical scheme adopted by the present invention is: a highly stable anisotropic conductive adhesive film, comprising the following components in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3-5 parts of meso-tetramethyl-meso-tetra-aminophenyl cup [4] pyrrole, 2-4 parts of N-vinyl oxazolidinone, 2-4 parts of bis (1-vinyl imidazole-2-) ketone, 1-3 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5 -(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione 3-5 parts, 1,4-diamino-2,3-dicyanoanthraquinone 1-3 parts, 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene 1-3 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.1-0.3 parts, conductive particles 5-15 parts, coupling agent 0.5-1 parts, initiator 1-2 parts, solvent 30-40 parts.
[0007] Preferably, there is no special requirement for the source of the acrylate-terminated hyperbranched silicone-modified polyurethane. In one embodiment of the present invention, the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of Chinese invention patent with authorization announcement number CN111393608B.
[0008] Preferably, the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0009] Preferably, the conductive particles are one or more selected from metal nickel balls, gold balls, nickel / gold balls, and resin microspheres plated with nickel and / or gold layers.
[0010] Preferably, the resin microspheres are any one of polystyrene microspheres, polyaniline microspheres, polymethyl methacrylate microspheres, polyacrylamide microspheres, polyvinyl alcohol microspheres, and polycaprolactone microspheres.
[0011] Preferably, the average diameter of the conductive particles is 3-40 μm.
[0012] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0013] Preferably, the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:(3-5).
[0014] Preferably, the solvent is any one of acetone, ethyl acetate, butanone, toluene, and N,N-dimethylformamide.
[0015] Another object of the present invention is to provide a method for preparing the highly stable anisotropic conductive adhesive film, comprising the following steps:
[0016] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0017] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film.
[0018] Preferably, the drying temperature is 85-95° C. and the drying time is 10-20 min.
[0019] Preferably, the thickness of the high-stability anisotropic conductive adhesive film is 10-60 μm.
[0020] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0021] (1) The method for preparing the highly stable anisotropic conductive adhesive film disclosed in the present invention has simple process, convenient and easy operation, high preparation efficiency and finished product qualification rate, low dependence on equipment, low energy consumption, suitable for continuous large-scale production, and has high promotion and application value.
[0022] (2) The highly stable anisotropic conductive adhesive film disclosed in the present invention comprises the following components in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3-5 parts of meso-tetramethyl-meso-tetra-aminophenyl cup [4] pyrrole, 2-4 parts of N-vinyl oxazolidinone, 2-4 parts of bis (1-vinyl imidazole-2-) ketone, 1-3 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propylene)-1,4-diol, 1,2-diol, 1,2-diol, 1,2-diol, 1,2-diol, 1,2-diol, 1,2-diol, 1,2-diol, 1,2-diol 3-5 parts of 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1-3 parts of 1,4-diamino-2,3-dicyanoanthraquinone, 1-3 parts of 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene, 0.1-0.3 parts of 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 5-15 parts of conductive particles, 0.5-1 parts of coupling agent, 1-2 parts of initiator, and 30-40 parts of solvent. Through the mutual cooperation between the components, the prepared high-stability anisotropic conductive adhesive film has high peeling strength, good conductivity, sufficient resistance to moisture and heat aging, and long service life.
[0023] (3) The high-stability anisotropic conductive adhesive film disclosed in the present invention, through the reasonable selection of the types and dosage ratios of various components, simultaneously introduces amino, ether bonds, ketone groups, morpholine groups, quinoxaline groups and hydroxyl groups formed by the ring opening of epoxy groups into the adhesive film, which are easy to form hydrogen bonds with the adhered interface and other effects, thereby effectively improving the peel strength; the selected components contain a large number of cyclic structures, such as imidazole groups, morpholine groups, triazine ketone groups, fluorenyl groups, and quinoxaline groups. These structures cooperate with each other, so that the cross-linked polymer has strong rigidity and a high glass transition temperature, thereby making the film more resistant to moisture and heat aging and more stable; 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione contains both epoxy groups and double bonds, which increases the crosslinking density. The system adopts double bond preliminary polymerization curing and epoxy hot pressing post-curing to form an interpenetrating network structure of the polymer, and the moisture and heat aging resistance of the polymer is greatly enhanced.
[0024] (4) The highly stable anisotropic conductive adhesive film disclosed in the present invention has a component containing unsaturated olefinic bonds that will undergo a preliminary curing reaction under the action of an initiator. At the same time, the component containing an epoxy group can also undergo an epoxy ring-opening reaction with the component containing an amino group through hot pressing during use, so that the adhesive film forms an interpenetrating network structure, thereby improving the modulus of the polymer. During the hot pressing process during use, the conductive particles can be fixed in the adhesive film layer without slipping, thereby avoiding short circuits. The contact between the particles in the vertical direction is closer, which can effectively improve the conductivity, further improve the stability, peel strength and moisture-heat aging resistance of the adhesive film, and further extend its service life. DETAILED DESCRIPTION
[0025] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0026] Example 1
[0027] A highly stable anisotropic conductive adhesive film, comprising the following components in parts by weight: 35 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3 parts of meso-tetramethyl-meso-tetra-p-aminophenyl cup [4] pyrrole, 2 parts of N-vinyl oxazolidinone, 2 parts of bis (1-vinyl imidazole-2-) ketone, 1 part of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propylene)-1,4-diol The mixture comprises 3 parts of 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1 part of 1,4-diamino-2,3-dicyanoanthraquinone, 1 part of 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene, 0.1 part of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 11 parts of conductive particles, 0.5 parts of coupling agent, 1 part of initiator and 30 parts of solvent.
[0028] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B; the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0029] The conductive particles are metal nickel balls; the average diameter of the conductive particles is 10 μm; the coupling agent is silane coupling agent KH550; the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:3; and the solvent is acetone.
[0030] A method for preparing the highly stable anisotropic conductive adhesive film comprises the following steps:
[0031] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0032] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film; the drying temperature is 85° C., and the drying time is 10 min; the thickness of the highly stable anisotropic conductive adhesive film is 25 μm.
[0033] Example 2
[0034] A highly stable anisotropic conductive adhesive film, comprising the following components in parts by weight: 37 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3.5 parts of meso-tetramethyl-meso-tetra-p-aminophenyl cup [4] pyrrole, 2.5 parts of N-vinyl oxazolidinone, 2.5 parts of bis (1-vinyl imidazole-2-) ketone, 1.5 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propylene)-1,4-diol The mixture comprises 3.5 parts of 1,4-diamino-2,3-dicyanoanthraquinone, 1.5 parts of 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene, 0.15 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 12 parts of conductive particles, 0.6 parts of coupling agent, 1.2 parts of initiator and 33 parts of solvent.
[0035] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B; the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0036] The conductive particles are gold balls; the average diameter of the conductive particles is 15 μm; the coupling agent is silane coupling agent KH560; the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:3.5; and the solvent is ethyl acetate.
[0037] A method for preparing the highly stable anisotropic conductive adhesive film comprises the following steps:
[0038] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0039] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film; the drying temperature is 87° C., and the drying time is 13 min; the thickness of the highly stable anisotropic conductive adhesive film is 25 μm.
[0040] Example 3
[0041] A highly stable anisotropic conductive adhesive film, comprising the following components in parts by weight: 40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 4 parts of Meso-tetramethyl-meso-tetra-p-aminophenyl cup [4] pyrrole, 3 parts of N-vinyl oxazolidinone, 3 parts of bis (1-vinyl imidazole-2-) ketone, 2 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propenyl) )-1,3,5-triazine-2,4,6(1H,3H,5H)-trione 4 parts, 1,4-diamino-2,3-dicyanoanthraquinone 2 parts, 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene 2 parts, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.2 parts, conductive particles 13 parts, coupling agent 0.7 parts, initiator 1.5 parts, solvent 35 parts.
[0042] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B; the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0043] The conductive particles are metal nickel balls; the average diameter of the conductive particles is 20 μm; the coupling agent is silane coupling agent KH570; the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:4; and the solvent is butanone.
[0044] A method for preparing the highly stable anisotropic conductive adhesive film comprises the following steps:
[0045] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0046] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film; the drying temperature is 89° C., and the drying time is 15 min; the thickness of the highly stable anisotropic conductive adhesive film is 25 μm.
[0047] Example 4
[0048] A highly stable anisotropic conductive adhesive film, comprising the following components in parts by weight: 43 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 4.5 parts of meso-tetramethyl-meso-tetra-p-aminophenyl cup [4] pyrrole, 3.5 parts of N-vinyl oxazolidinone, 3.5 parts of bis (1-vinyl imidazole-2-) ketone, 2.5 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propylene)-1,4-diol The mixture comprises 4.5 parts of 1,4-diamino-2,3-dicyanoanthraquinone, 2.5 parts of 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene, 0.25 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 14 parts of conductive particles, 0.9 parts of coupling agent, 1.8 parts of initiator and 38 parts of solvent.
[0049] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B; the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0050] The conductive particles are gold balls; the average diameter of the conductive particles is 25 μm; the coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:2:3; the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:4.5; and the solvent is toluene.
[0051] A method for preparing the highly stable anisotropic conductive adhesive film comprises the following steps:
[0052] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0053] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film; the drying temperature is 92° C., and the drying time is 17 min; the thickness of the highly stable anisotropic conductive adhesive film is 25 μm.
[0054] Example 5
[0055] A highly stable anisotropic conductive adhesive film comprises the following components in parts by weight: 45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 5 parts of meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, 4 parts of N-vinyl oxazolidinone, 4 parts of bis (1-vinyl imidazole-2-) ketone, 3 parts of N-acryloyl morpholine, 5 parts of 1,3-bis (oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6 (1H,3H,5H)-trione, 3 parts of 1,4-diamino-2,3-dicyanoanthraquinone, 3 parts of 9,9-bis [(2,3-epoxypropoxy) phenyl] fluorene, 0.3 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 15 parts of conductive particles, 1 part of a coupling agent, 2 parts of an initiator, and 40 parts of a solvent.
[0056] The acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B; the preparation method of the meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole is described in: Guo Yong, Shao Shijun, He Lijun, et al. Synthesis and Characterization of Meso-tetramethyl-meso-tetraaminophenylcalix[4]pyrrole [J]. Chemical Reagents, 2002(6):344-345.
[0057] The conductive particles are metal nickel balls; the average diameter of the conductive particles is 30 μm; the coupling agent is silane coupling agent KH550; the initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:5; and the solvent is N,N-dimethylformamide.
[0058] A method for preparing the highly stable anisotropic conductive adhesive film comprises the following steps:
[0059] Step S1, mixing the components uniformly by weight to obtain a conductive adhesive;
[0060] Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film; the drying temperature is 95° C., and the drying time is 20 min; the thickness of the highly stable anisotropic conductive adhesive film is 25 μm.
[0061] Comparative Example 1
[0062] A highly stable anisotropic conductive adhesive film and a preparation method thereof are basically the same as those in Example 1, except that p-phenylenediamine is used instead of Meso-tetramethyl-meso-tetra-p-aminophenylcalix[4]pyrrole and N-acryloylmorpholine.
[0063] Comparative Example 2
[0064] A highly stable anisotropic conductive adhesive film and a preparation method thereof are basically the same as those in Example 1, except that p-phenylenediamine is used instead of 1,4-diamino-2,3-dicyanoanthraquinone and 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline.
[0065] In order to further illustrate the beneficial technical effects of the highly stable anisotropic conductive adhesive films involved in the embodiments of the present invention, relevant performance tests were conducted on the highly stable anisotropic conductive adhesive films involved in Examples 1-5 and Comparative Examples 1-2; the test results are shown in Table 1, and the test method is as follows:
[0066] (1) 90° peel strength: Each conductive film was placed between the ITO glass and the flexible circuit and pressed using a K-880C constant temperature hot press; the pressing pressure was 0.1 MPa; the temperature was 150°C; the time was 15 s, and the post-processing temperature was 25°C (the bonding width × length was 28 mm × 38 mm). The peel strength between the conductive film and the ITO glass and the flexible circuit was tested using a 5969 electronic universal material testing machine from Instron, USA, at a peeling speed of 10 mm / min.
[0067] (2) Resistance to moisture and heat aging: Each high-stability anisotropic conductive adhesive film was placed in an environment of 85°C and 85% relative humidity for 1000 hours. After cooling to room temperature, the 90° peel strength was tested again according to the method in (1), and the retention rate of the 90° peel strength was calculated. The larger the value, the better the resistance to moisture and heat aging.
[0068] (3) On-resistance: Use a Keithley resistance meter to test the resistance using the four-probe method.
[0069] As can be seen from Table 1, the high-stability anisotropic conductive adhesive films involved in the embodiments of the present invention have better peel strength, moisture-heat aging resistance, and good conductivity than the comparative example products. The combined use of meso-tetramethyl-meso-tetraaminophenyl cup [4] pyrrole, N-acryloylmorpholine, 1,4-diamino-2,3-dicyanoanthraquinone and 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline is beneficial to improving the above properties.
[0070] Table 1
[0071] project 90° peel strength On-resistance Resistance to moisture and heat aging unit N / cm Ω % Example 1 12.5 0.10 99.27 Example 2 12.8 0.15 99.49 Example 3 13.0 0.17 99.69 Example 4 13.5 0.19 99.94 Example 5 13.7 0.20 99.99 Comparative Example 1 9.9 0.15 95.38 Comparative Example 2 10.6 0.13 94.15
[0072] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly stable anisotropic conductive adhesive film, characterized in that: The invention comprises the following components in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3-5 parts of meso-tetramethyl-meso-tetra-p-aminophenyl cup [4] pyrrole, 2-4 parts of N-vinyl oxazolidinone, 2-4 parts of bis (1-vinyl imidazole-2-) ketone, 1-3 parts of N-acryloyl morpholine, 1,3-bis (oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine ... 3-5 parts of oxazine-2,4,6(1H,3H,5H)-trione, 1-3 parts of 1,4-diamino-2,3-dicyanoanthraquinone, 1-3 parts of 9,9-di[(2,3-epoxypropoxy)phenyl]fluorene, 0.1-0.3 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 5-15 parts of conductive particles, 0.5-1 parts of coupling agent, 1-2 parts of initiator, and 30-40 parts of solvent.
2. The highly stable anisotropic conductive adhesive film according to claim 1, characterized in that: The conductive particles are selected from one or more of metal nickel balls, gold balls, nickel / gold balls, and resin microspheres with nickel and / or gold layers on their surfaces.
3. The highly stable anisotropic conductive adhesive film according to claim 2, characterized in that: The resin microspheres are any one of polystyrene microspheres, polyaniline microspheres, polymethyl methacrylate microspheres, polyacrylamide microspheres, polyvinyl alcohol microspheres, and polycaprolactone microspheres.
4. The highly stable anisotropic conductive adhesive film according to claim 1, characterized in that: The average diameter of the conductive particles is 3-40 μm.
5. The highly stable anisotropic conductive adhesive film according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.
6. The highly stable anisotropic conductive adhesive film according to claim 1, characterized in that: The initiator is a mixture of dibenzoyl peroxide and azobisisobutyronitrile in a mass ratio of 1:(3-5).
7. The highly stable anisotropic conductive adhesive film according to claim 1, characterized in that: The solvent is any one of acetone, ethyl acetate, butanone, toluene and N,N-dimethylformamide.
8. A method for preparing a highly stable anisotropic conductive adhesive film according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, mixing the components uniformly by weight to obtain a conductive adhesive; Step S2, degassing the conductive adhesive, preparing a wet film using a wet film preparation device, and drying to obtain a highly stable anisotropic conductive adhesive film.
9. The method for preparing a highly stable anisotropic conductive adhesive film according to claim 8, characterized in that: The drying temperature is 85-95° C. and the drying time is 10-20 min.
10. The method for preparing a highly stable anisotropic conductive adhesive film according to claim 8, characterized in that: The thickness of the highly stable anisotropic conductive adhesive film is 10-60 μm.
Citation Information
Patent Citations
High-temperature-resistant conductive adhesive film and preparation method thereof
CN116948558A
